Do Dutch Dentists Extract Monopoly Rents? - Nadine Ketel; Edwin Leuven; Hessel Oosterbeek; Bas van der Klaauw (Institute of Labor Economics (IZA), 2018)
We exploit admission lotteries to estimate the payoffs to the dentistry study in the Netherlands. Using data from up to 22 years after the lottery, we find that in most years after graduation dentists earn around 50,000 Euros more than they would earn in their next-best profession. The payoff is larger for men than for women but does not vary with high school GPA. The large payoffs cannot be attributed to longer working hours, larger human capital investments or sacrifices in family outcomes. The natural explanation is that Dutch dentists extract a monopoly rent, which we attribute to the limited supply of dentists in the Netherlands. We discuss policies to curtail this rent.
Keywords: J44; I18; I23; C36; 330; dentists; returns to education; monopoly rents; random assignment